2016
DOI: 10.1073/pnas.1617824113
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the neuropeptide galanin system in major depressive disorder involve levels of transcripts, methylation, and peptide

Abstract: Major depressive disorder (MDD) is a substantial burden to patients, families, and society, but many patients cannot be treated adequately. Rodent experiments suggest that the neuropeptide galanin (GAL) and its three G protein-coupled receptors, GAL 1-3 , are involved in mood regulation. To explore the translational potential of these results, we assessed the transcript levels (by quantitative PCR), DNA methylation status (by bisulfite pyrosequencing), and GAL peptide by RIA of the GAL system in postmortem bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 144 publications
(150 reference statements)
5
57
0
Order By: Relevance
“…This phenotype could be rescued by knocking down expression of this receptor. This is further underscored by recent findings showing increased GalR1 levels (measured by qPCR) in the DRN/vPAG in human depressed suicides versus controls (Barde et al, 2016). These results lend further weight to the present findings observed in the mbTBI.…”
Section: Paper Ii: the Galanin System And Mbtbisupporting
confidence: 83%
See 1 more Smart Citation
“…This phenotype could be rescued by knocking down expression of this receptor. This is further underscored by recent findings showing increased GalR1 levels (measured by qPCR) in the DRN/vPAG in human depressed suicides versus controls (Barde et al, 2016). These results lend further weight to the present findings observed in the mbTBI.…”
Section: Paper Ii: the Galanin System And Mbtbisupporting
confidence: 83%
“…For the Ribo-ISH the sectioned tissues were first fixed for 10 min in cold 4% paraformaldehyde in 0.1 M sodium phosphate buffer (PBS), pH 7.4, followed by 5 The optimal exposure time was determined by exposing the slides to imaging plates (BAS-SR Fujifilm, Tokyo, Japan) for 24 h at RT, which were scanned using a phosphoimager (Fuji BAS 3000, Tokyo, Japan). Based on this data, TPH2 slides were developed after 72 h, galanin and TH typically after one week, and GalR1 after 8-12 weeks using D19 developer (Kodak) and AL-4 fixative (Kodak) and mounted in glycerolphosphate buffer.…”
Section: In Situ Hybridisation (Ish)mentioning
confidence: 99%
“…Human genetic studies have shown the involvement of the galanin system in pshychiatric disorders and MDD (Barde et al . ). GAL and GALR1 have CRE binding sites (Zachariou et al .…”
Section: Discussionmentioning
confidence: 97%
“…Even if these neuroactive substances were ubiquitously co‐released, then the receptor repertoire of their cellular targets could diversify their action. Ultimately, ependymal cells could thus produce temporary neuropeptide constellations for volume transmission whose differential binding and output modulation in nearby midbrain and hindbrain structures could account for substantial functional heterogeneity and explain key features of neuropeptide contributions to anxiety and depression (Belzung et al , 2006; Barde et al , 2016). …”
Section: Discussionmentioning
confidence: 99%